Identification of a novel microdeletion at 9q21.13 in a family with epilepsy, intellectual disability, and speech disorders and literature review - Jiang, Liqing; Li, Jiaqi; Han, Aizhong; Hou, Fei; Wei, Xiaotong; Tian, Yanjun (Frontiers in Genetics, 2025)
BackgroundAt present, there are few reports on 9q21.13 microdeletion syndrome, which is characterized by intellectual disability, epilepsy, autistic behaviour, and recognizable facial features, etc. The aim of this study is to enrich the phenotypic features of 9q21.13 microdeletion syndrome and expand the possible segments of 9q21.13 microdeletion syndrome.MethodsFour individuals from a 3-generation Chinese family with epilepsy, intellectual disability, and speech disorders were recruited in this study. Whole exome sequencing (WES) and chromosome microarray analysis (CMA) techniques were used for genetic testing. The pathogenicity of CNVs was interpreted following the American College of Medical Genetics (ACMG) standards and guidelines.ResultsA 9q21.13 microdeletion with a fragment size of approximately 2.35 Mb was identified in the proband, the proband’s mother and grandmother and even the fetus. And this region encompasses 6 protein coding genes, namely, ALDH1A1, ANXA1, GDA, RORB, TMC1, and ZFAND5.ConclusionIn this article, we report a girl with epilepsy, intellectual disability, speech disorders, delayed motor development, and autism. We identified a novel 9q21.13 microdeletion with a fragment size of approximately 2.35 Mb in 4 individuals from a 3-generation Chinese family by WES and CMA techniques. Within the region, the RORB gene is a strong candidate gene for complex neurodevelopmental disorders. Herein, we speculate that RORB makes a significant contribution to the clinical phenotypes caused by 9q21.13 microdeletion.